PERANCANGAN MERS UNTUK PENGENDALIAN TEGANGAN PADA GENERATOR INDUKSI TERHADAP PERUBAHAN BEBAN - , SHOLIHATTA AZIZ KUSUMAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The use of renewable energy as an alternative energy source is getting the major project to reduce dependence on fossil energy sources. In general, the renewable energy power plant using induction machine types. But it has the disadvantage that the voltage regulation of induction generator is bad. In this research, MERS has been made to control the load voltage and the voltage generator. MERS is an acronym of the magnetic energy recovery switch. The working principle of MERS is absorb and release of magnetic energy back. The switch in this case is a MOSFET is coupled in h-bridge can control charging the capacitor that is by turning on ( turn on ) and off ( turn off ), then the capacitor as power compensator magnetic energy producers determine the amount of reactive power supplied to the inductive load. Stages in this research are study the literature, perform simulations in PSIM, doing hardware design, doing program design, internal testing MERS, MERS testing on SEIG (self-excited induction generator ), data collection and writing the report. From the test results proved that MERS can be used to control the voltage at the generator terminals and the voltage at the load . Additionally MERS can be used to control power flow.